Peningkatan Kreativitas Guru Dalam Melaksanakan Praktikum Melalui Pelatihan di SMAN 3 Toraja Utara - Agustina Minggu (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2021)
Teachers as educators, teachers are required to be more creative in carrying out learning activities for their students. For matters related to this, it is very important for teachers to have broader insights and high creativity. In carrying out its activities, a teacher must have ideas to improve thinking power because the 2013 curriculum that we use today demands teacher creativity in the learning process, especially in developing innovative learning models, especially when carrying out practicals. Being a creative teacher, carrying out practicum not only in the laboratory but in the environment around us can be a place to carry out practice by utilizing materials from the natural environment around us. Strategies to increase teacher creativity in carrying out practicum through various teacher competency improvement programs. Therefore, to increase the creativity of teachers in carrying out practicum at SMAN 3 Toraja Utara, it is necessary to hold regular training/workshops given to teachers so that they can actualize themselves and increase creativity. In addition, schools need to intensify peer-to-peer programs, namely the socialization program for the results of training that are attended by teachers and imparted to teachers in the school environment in order to obtain the same knowledge and information.